Hubungan Pengetahuan Ibu Menyusui Tentang Cara Perawatan Luka Perineum Dengan Infeksi Luka Perineum Di Klinik Siti Kholijah Medan Tahun 2018 - Suwardi, Suyanti; Mouliza, Nurul (Window of Health : Jurnal Kesehatan, 2019)
According to the WHO infection is one of the causes of maternal death in the proportion of 20-30% and by 25-55% of cases of infection caused by birth infections or episiotomy. Perineal rupture cases in maternal mothers in the world in 2015 were 2.7 million and estimated to reach 6.3 million in 2050. In Dr. Pirngadi Medan in 2010 as reported by AsroelBiryn and friends, there are 270 perineal ruptures from 385 deliveries. Objective This study aims to find out about postpartum maternal knowledge about Perineal Suture Treatment with Perineal Wound Infection at the Siti Kholijah Clinic in Medan in 2018. Method This type of research uses analytical survey with cross sectional approach. The population in this study were postpartum postpartum mothers at the Siti Kholijah Clinic and experienced 46 perineal wounds and the entire population sampled. The data used is primary data. Statistical test uses chi-square.Results The results of the study used chi-square statistical test on the relationship of postpartum mothers' knowledge about the treatment of perineal wounds with p-value perineal wound infection of 0.000 <Î± 0.050, with the most experienced perineal wound infections were less knowledgeable mothers, namely 22 respondents (47.8% ) and those with sufficient knowledge are 2 respondents (4.3%).Conclusion The conclusion of this study is that there is a relationship between postpartum mothers' knowledge about the treatment of perineal wounds with perineal wound infection in the Siti Kholijah Clinic in Medan in 2018.